The relationship between ACE insertion/deletion polymorphism and coronary artery disease with or without myocardial infarction - Seckin, D; Ilhan, N; Ilhan, N; Ozbay, Y (Pergamon-Elsevier Science Ltd, 2006)
Objectives: Presence of the D allele or homozygosity for the deletion (D) allele of the angiotensicen-converting enzyme (ACE) insertion/ deletion (I/D) polymorphism has been discussed as potent risk factor for coronary artery disease (CAD) and myocardial infarction (MI). The D allele is associated with higher levels of circulating ACE and therefore may predispose one to cardiovascular damage. Design and methods: The study presented here was performed to investigate the association between the ACE genotype and ACE levels. The study group was comprised of 118 angiographically verified CAD patients. 65 patients were MI (+) and 53 patients were MI (-) in this group. A total of 70 healthy individuals were taken as controls. Genomic DNA of 188 subjects was extracted from whole blood. The polymerase chain reaction was used for ACE genotyping, and ACE levels were measured by ELISA. Results: The D allele was found to be significantly more frequent in patients with MI (+) compared with controls (P = 0.024). ACE levels were significantly higher in both MI (-) and MI (+) groups with CAD patients than in controls (P < 0.005). Plasma ACE level was higher in all three groups in the DD genotype compared to II genotype. In groups I and III, this was statistically significant (P < 0.0001, P < 0.01). Conclusions: It was shown that the I/D polymorphism in the gene for ACE is a genetic risk factor for CAD patients who have a history of MI. ACE insertion/deletion gene polymorphism is also associated with plasma ACE levels in CAD patients with a history of MI. (c) 2005 The Canadian Society of Clinical Chemists. All rights reserved.
Keywords: coronary artery disease; myocardial infarction; ACE I/D gene polymorphism